2021
DOI: 10.1016/j.apmr.2021.01.080
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Higher Treatment Outcome Expectations Are More Satisfied With the Results of Nonoperative Treatment for Thumb Base Osteoarthritis: A Cohort Study

Abstract: To investigate how satisfaction with treatment outcome is associated with patient mindset and Michigan Hand Outcome Questionnaire (MHQ) scores at baseline and 3 months in patients receiving nonoperative treatment for first carpometacarpal joint (CMC-1) osteoarthritis (OA). Design: Cohort study Setting: A total of 20 outpatient locations of a clinic for hand surgery and hand therapy in the Netherlands. Participants: Patients (NZ308) receiving nonoperative treatment for CMC-1 OA, including exercise therapy, an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 54 publications
4
12
0
Order By: Relevance
“…This is especially noteworthy because several studies have suggested that clinicians ought to try to temper patients’ expectations [14, 20, 30, 52], and many surgeons believe that it is important to help patients to cultivate reasonable expectations before surgery. By contrast, several other studies have suggested that boosting expectations is associated with better outcomes [12, 17, 28, 36, 37, 47]. Our findings support the latter suggestion.…”
Section: Discussionsupporting
confidence: 85%
“…This is especially noteworthy because several studies have suggested that clinicians ought to try to temper patients’ expectations [14, 20, 30, 52], and many surgeons believe that it is important to help patients to cultivate reasonable expectations before surgery. By contrast, several other studies have suggested that boosting expectations is associated with better outcomes [12, 17, 28, 36, 37, 47]. Our findings support the latter suggestion.…”
Section: Discussionsupporting
confidence: 85%
“…47,49 Overall, improvements noted in clinical practice are likely mediated by positive treatment expectations rather than the type of intervention. 53 Therefore, providing patients with a positive outlook on their pathology, and avoiding inducing fear avoidance and catastrophising thoughts in our clients, is likely going to benefit them. This review presents several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…But satisfaction after nonoperative treatment of first CMC osteoarthritis is not yet optimal, positive expectations of treatment outcomes are associated with higher satisfaction. Therefore, optimizing patient expectations may further improve treatment expectations and outcomes [5,6]. In another systematic review and meta-analysis which included 11 RCTs, Marotta et al compared the effectiveness of 4 different orthoses (short thermoplastic CMC splint, long thermoplastic CMC-metacarpophalangeal [MCP] splint, short neoprene CMC splint, and long neoprene CMC-MCP splint) with that of no splinting for first CMC osteoarthritis.…”
Section: Handmentioning
confidence: 99%